Examining the effect of binge eating and disinhibition on compensatory changes in energy balance following exercise among overweight and obese women. (August 2016) - Emery, Rebecca L.; Levine, Michele D.; Jakicic, John M.
Abstract: Some women behaviorally compensate for the energy expended during exercise by increasing their energy intake or becoming more sedentary, thereby decreasing their energy expenditure. Although behavioral compensation can attenuate or even reverse the energy deficit generated by exercise, few data are available on predictors of compensatory responses to exercise. The present study aimed to identify eating-related predictors of compensatory changes in energy balance following exercise. Overweight and obese, physically inactive women ( N = 48) completed self-report measures of disinhibition and binge eating and participated in two experimental conditions, exercise and rest, in counterbalanced order. Energy intake and expenditure were measured for 24-hours following each experimental condition to estimate energy balance. On average, women were 21.33 ± 2.09 years old and 63% were white. Of the sample, 63% compensated for the energy expended during exercise by increasing their energy intake or decreasing their energy expenditure. Linear mixed effects modeling with repeated measurement showed that disinhibition was not predictive of behavioral compensation. However, there was a significant difference between the negative energy balance observed following the rest condition and the positive energy balance observed following the exercise condition among women who reported binge eating, which was driven by a tendency to spend less time being physically active and more time being sedentary following exercise. These findings indicate that women who binge eat may be at greatest risk of compensating for exercise. Future research is needed to better understand psychosocial predictors and common mechanisms through which behavioral compensation is promoted. Highlights: We assessed predictors of compensatory changes in energy balance after exercise. The majority of the sample behaviorally compensated for exercise. Disinhibition was not predictive of behavioral compensation. Binge eating predicted compensatory increases in energy balance.